Cancer Dynamics - Gandía, Daniel (2020)
Even though cancer researchers nowadays are trying to develop many key cellular pathways susceptible to be tackled by therapeutic approaches, we are far from being able to consider some cancers as curable diseases in general terms. From a pharmacodynamic point of view, the main potential molecular targets involved are driver oncogenes, tumor suppressor genes, growth factors and their receptors, transcription factors, tyrosine kinases, and cell adhesion molecules. If we consider possible targets at higher organization levels, we can intervene in aspects such as chromatin organzation, tumor microenvironment, angiogenesis, apoptosis, senescence, mitochondria metabolism, and immune pathways.